Analysis of Community Health Service Management and Individual Health Efforts at Community Health Centers: A Qualitative Study - Detriana Imeriet Nenobais; Anastasia Yashinta Theedens; Roswita Sari Kaka (Jurnal EduHealth, 2026)
Community Health Centers (Puskesmas), as first-level health care facilities, play a strategic role in providing Community Health Efforts (UKM) and Individual Health Efforts (UKP). The integration and effectiveness of these two efforts are largely determined by the quality of service management. This study aims to analyze the management of UKM and UKP services at Community Health Centers through a qualitative approach. The study was conducted at three community health centers (Puskesmas) in Southwest Sumba Regency in 2025. Data collection techniques included in-depth interviews, participant observation, and document review. Informants included the heads of the community health centers, community-based health unit (UKM) coordinators, community-based health unit (UKP) coordinators, health workers, and community representatives. Data analysis was conducted using thematic analysis through data reduction, categorization, and conclusion drawing. The results indicate that management functions (planning, organizing, implementing, and evaluating) have been implemented, but are not fully based on community needs. Key challenges include limited human resources, administrative burdens, suboptimal cross-program coordination, and suboptimal data utilization. The integration of SMEs and UKPs remains administrative and not yet fully operational. Strengthening managerial capacity, optimizing information systems, and increasing public participation are key strategies for improving service quality.